ENHANCING STUDENTS’ READING ACHIEVEMENT BY USING PROFESSOR KNOW-IT-ALL STRATEGY - Mimiliah; Dewi Sartika (Universitas Islam Ogan Komering Ilir Kayuagung, 2016)
Students still have difficulty in comprehending the reading text. Hence, the objective of the study was to find out whether Professor Know-It-All strategy could improve the tenth-grade students’ reading achievement at SMA Meranti Pedamaran or not. The population of this study was all the tenth-grade students of SMA Meranti Pedamaran. The sample was chosen using purposive sampling method, therefore, two classes; experimental group (class X.3) and control group (class X.2) were taken as the samples and each of them consisted of 36 students. To conduct this study, the quasiexperimental method was used. The written test in the form of multiple choices was administered in order to collect the data. The test was tried out to nonsample students at SMA Meranti Pedamaran in order to know the reliability and validity of the test. Before analyzing the data using the t-test, the normality and homogeneity were found. After the data were considered normal and homogenous, the result of independent sample t-test showed that t-obtained (4.960) was higher than ttable (1.9944) and pvalue (0.000) was less than ᾳvalue (0.05), it showed that null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It meant that Professor Know-It-All strategy could improve the tenth-grade students’ reading achievement at SMA Meranti Pedamaran. In brief, Professor Know-It-All Strategy could improve students’ reading achievement because this strategy guided them to comprehend the reading texts given during the treatment by asking and answering the questions posed by their classmates